Hypothalamic circuits regulating appetite and energy homeostasis: pathways to obesity - Katharina Timper; Jens C. Brüning (The Company of Biologists, 2017)
The 'obesity epidemic' represents a major global socioeconomic burden that urgently calls for a better understanding of the underlying causes of increased weight gain and its associated metabolic comorbidities, such as type 2 diabetes mellitus and cardiovascular diseases. Improving our understanding of the cellular basis of obesity could set the stage for the development of new therapeutic strategies. The CNS plays a pivotal role in the regulation of energy and glucose homeostasis. Distinct neuronal cell populations, particularly within the arcuate nucleus of the hypothalamus, sense the nutrient status of the organism and integrate signals from peripheral hormones including pancreas-derived insulin and adipocyte-derived leptin to regulate calorie intake, glucose metabolism and energy expenditure. The arcuate neurons are tightly connected to other specialized neuronal subpopulations within the hypothalamus, but also to various extrahypothalamic brain regions, allowing a coordinated behavioral response. This At a Glance article gives an overview of the recent knowledge, mainly derived from rodent models, regarding the CNS-dependent regulation of energy and glucose homeostasis, and illustrates how dysregulation of the neuronal networks involved can lead to overnutrition and obesity. The potential impact of recent research findings in the field on therapeutic treatment strategies for human obesity is also discussed.